ANALISIS MANAJEMEN SUMBER DAYA MANUSIA, KOMUNIKASI INTERPERSONAL DAN PENGENDALIAN INTERNAL TERHADAP EFEKTIVITAS PELAYANAN KESEHATAN DI RSUD PROVINSI SUMSEL - Paramitha Sari Dwi Saputri (Universitas Bina Taruna Gorontalo, 2023)
This study aims to analyze human resource management, interpersonal communication and internal control on the effectiveness of health services at the South Sumatra Prov Hospital. This research uses the mixed method method. This study used questionnaire data collection techniques, interviews and observations. Research results 1) Overall the variable of human resource management with an average percentage of 80.43%, which means that the HR management in the South Sumatra Prov Hospital is very good at carrying out its duties. Second, interpersonal communication with an average percentage of 83.34%, which means that communication in the Sumsel Prov Hospital in South Sumatra is going very well, be it between employees or direct communication with superiors. Internal control with an average percentage of 84.42%, which means that everything is going well and is in accordance with existing SOPs. Then, the effectiveness of health services obtained an average percentage of 85.88%, which means that the services provided have been carried out as optimally as possible so that everyone can get the best service from the South Sumatra Prov Hospital. 2) Efforts made to increase the effectiveness of health services at the Sumsel Prov Hospital are carried out by the management of Human Resources, in this case health workers and other employees. Maintain good interpersonal communication, between employees or employees and the hospital. Then, the implementation of internal control at the Sumsel Prov Hospital in order to provide health services properly and in accordance with applicable regulations.